Application of Fuzzy Logic for Sensory Evaluation Analysis of Commercial Soymilks - Wahyu Putri; Hadi Munarko; Ajeng Astrini Brahmanti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Soymilk is a plant-based beverage that widely consumed due to its nutritional value. However, differences in formulation among commercial products may lead to variation in sensory quality and consumer acceptance. This study evaluated the sensory characteristic and consumer preference of five commercially available soymilk using fuzzy logic approach. Sensory assessment was conducted with 26 semi-trained panellists who evaluated six quality attributes: colour, aroma, viscosity, taste, mouthfeel, and aftertaste, using linguistic scales. The collected responses were converted into triangular fuzzy numbers for analysis. The results showed that the commercial product exhibits differences in acceptance levels, with the preference ranking S4 > S2 > S3 > S5 > S1. Taste was identified as the most influential factor in consumer acceptance with a similarity value of 0,8426, followed by mouthfeel (0,8265) that categorized as highly important. Meanwhile, color (0,9702), viscosity (0,9497), aroma (0,8318), and aftertaste (0,7954) were categorized as important. These findings indicate that fuzzy logic is a useful analytical tool for handling uncertainty in sensory evaluation and can provide practical insight for the development and optimization of commercial plant-based beverages. Contribution to Sustainable Development Goals (SDGs):SDG 2: Sustainable Food Production And Resilient AgriculturalSDG 3: Good Health and Well-BeingSDG 12: Sustainable Management And Efficient Use Of Natural Resources